Foreign workers and human rights violations: Malaysia’s response to COVID-19 and the way forward - Mafuzah Mohamad,; Jady Zaidi Hassim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Foreign workforce has significantly contributed to Malaysia’s economy, and this country has been relying on them for decades. Unfortunately, Malaysia was already entangled with the country’s treatment of foreign workers even before the onset of COVID-19. As a government suppression attempt to flatten the COVID-19 pandemic curve, Malaysian efforts to deal with the situation seem to be at the lowest point. Despite the government’s commitment not to detain them throughout the screening process, foreign workers have been held in immigration depots regardless of their legal status. In addition, the overcrowded immigration depot makes it hard to exercise physical distance, hampers the quarantine process, and unequal health care facilities in detention centres. This situation captured worldwide attention since it violated human rights legislation. The protection of workers’ rights is also in tandem with the United Declaration of Human Rights and Sustainable Development Goals 2030 (SDG) 8.8, encouraging and ensuring everyone’s right to a safe and healthy workplace is protected. This paper employed thematic analysis using ATLAS.ti 9 software to evaluate the government’s suppression efforts and human rights violations during COVID-19. The findings propose numerous suggestions, including an emergency review of the admission process for foreign workers to Malaysia. The inconsistency in the government policy had hampered the country’s mission of becoming a developed nation. It thus hindered the advancement of innovation and technology, as in the Twelfth Malaysian Plan and Sustainable Development Goals 2030.